IMPLEMENTASI KEBIJAKAN BANTUAN HIBAH BIDANG KEAGAMAAN DI BIRO ADMINITRASI KESEJAHTERAAN RAKYAT SEKRETARIAT DAERAH PROVINSI RIAU TAHUN 2017 - Shinta Devina Putri; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Grants are a form of funds that are channeled to the public which are sourced from regional budget revenues and expenditures that are not obligatory and not binding on an ongoing basis which aims to support the implementation of regional government affairs. Policy implementation that has not been guided by policy standards and objectives, raises various problems. Among them are the slow follow-up of verification of proposals, and the absence of a definite policy regarding the schedule of religious aid grant activities. This study uses a qualitative approach. Data collection techniques are carried out with involved observations, in-depth interviews and documentation. Indicators of Implementation of Religious Sector Grants Assistance Policies include (1) Religious Coordination Meeting, (2) Selection Process of Management Requests to the People's Welfare Administration Bureau, (3) Monitoring of the Implementation of Religious Aid Grants, (4) Budgeting for Religious Grants, (5) Distribution of Religious Grants, (6) Accountability Reports by Governors and Government Parties. The concept of influencing factors uses Van Metter and Van Horn theory in Agustino (2016). From the results obtained in the research on the implementation of religious aid grant policy in the public welfare administration bureau there are still many things that influence the implementation of this policy. The influencing factors are (1) size and purpose of the policy, (2) resources, (3) inter-organizational communication, (4) economic, social and political environment.Keywords: Implementation, Policy, Grant Funding